A Study on the Influence of Induced Water Stress on Seeds Germination and Seedlings Growth of Silybum marianum - AI-Aiwani, M. A. M (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The effect of water stress induced by using polyethylene glycol (PEG-6000) on germination of seeds and growth of seedlings of Silybum marianum was studied.  Two  concentrations  of PEG  were used to get two water stresses (-0.4 & -0.8 bar) as well as the control for comparison. The results showed a significant decrease (P